E-learning Platform and Pedagogical Monitoring in the Context of Digital Transformation - A. V. Khaperskaya; М. G. Minin (Высшее образование в России)
Upholding the quality of education in the absence of face-to-face contact requires an environmental approach and the creation of the unified online space and eLearning platform. The article makes the case for the relevance of creating automated tools for assessing the existing competencies of a listener necessary to form an individual learning route. The authors have developed methods for providing an automated pedagogical monitoring, described the principles of work of the automated diagnostic systems, and also gave the examples of its implementation. The suggested method combining key words and Template matching enables to optimize the eLearning platform. The article considers the possibilities of the system of automated pedagogical monitoring application when using the case technologies and students’ project work remotely in an electronic environment. In particular, the implementation of an expert assessment method using image theory and machine learning is presented. The article argues that electronic didactics makes it possible to expand the functionalities of pedagogical monitoring in conditions of digitalization, while maintaining the principles of traditional pedagogy. Taking into account the fact that there is a huge variety of different foreign and domestic aggregators of online courses it is necessary to develop a technology providing a selection of on-demand courses to reduce the time expenditure.